2008
DOI: 10.1007/s00705-007-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

T-even-related bacteriophages as candidates for treatment of Escherichia coli urinary tract infections

Abstract: Multidrug-resistant uropathogenic Escherichia coli (UPEC) is increasing gradually on a worldwide scale. We therefore examined the possibility of bacteriophage (phage) therapy for urinary tract infections (UTIs) caused by the UPEC strains as an alternative to chemotherapy. In addition to the well-known T4 phage, KEP10, which was newly isolated, was used as a therapeutic phage candidate. KEP10 showed a broader bacteriolytic spectrum (67%) for UPEC strains than T4 (14%). Morphological and genetic analyses showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 23 publications
3
57
1
1
Order By: Relevance
“…The observed 70% reduction of Cronobacter colonies in the kidneys 24 hours after a single phage dose is consistent with other similar results observing phage efficacy in the treatment of wound infections [32]. The ability of phages to survive in the urinary tract 24 hours after administration has already been shown [33]. There was no difference in Cronobacter colonization of the bladder between treated and infected groups.…”
Section: Discussionsupporting
confidence: 90%
“…The observed 70% reduction of Cronobacter colonies in the kidneys 24 hours after a single phage dose is consistent with other similar results observing phage efficacy in the treatment of wound infections [32]. The ability of phages to survive in the urinary tract 24 hours after administration has already been shown [33]. There was no difference in Cronobacter colonization of the bladder between treated and infected groups.…”
Section: Discussionsupporting
confidence: 90%
“…Whether different phages have various abilities to resist human serum inactivation remains to be evaluated; we suggest that future assessments of experimental phage therapy should include this evaluation. Pharmacokinetic properties of phage in experimental models using adult mice have been described previously (19,31,36,40,44) but, to our knowledge, they have never been studied in a neonatal murine model. Our data indicated that EC200 PP was partially retained by spleen and kidney, where phage concentrations were at any time as high or higher than in blood, especially after intraperitoneal injection, as in mouse models (19,31,36).…”
Section: Discussionmentioning
confidence: 98%
“…Though used for decades in Eastern Europe, successful phage therapy has been demonstrated only recently in experimental models (8,11,15,27,36,40,43,44). Because bacteriophage replicate at infection sites, efficacy may require just a single dose (23,40).…”
mentioning
confidence: 99%
“…After seven days, 100 and 90% of mice treated with T4 and KEP10, respectively, had survived. In the control group, where no phages were administered, all the mice died within three days [78]. In addition, lower multiplicities of infection (0.03 and 0.003) resulted in a reduced rescue of animals (60 and 40%) [79].…”
Section: Phages Therapy In Animal Models Of Human Infectionmentioning
confidence: 99%